Investigating the impact of cigarette smoke on the immunopathogenesis of chronic respiratory disease - Cass, Steven P (My University, 2021)
Cigarette smoke is an insidious insult that is associated with a spectrum of respiratory diseases that range from cancer to obstructive diseases such as chronic obstructive pulmonary disease (COPD), to restrictive diseases such as idiopathic pulmonary fibrosis (IPF). In this thesis, we explore how cigarette smoke impacts immune components that contribute to respiratory disease. To begin, we assessed the impact of cigarette smoke on airway antibody and autoantibody levels. We assessed sputum, a non-invasive method to sample the lower airways, to directly assess the presence of antibodies and autoantibodies in COPD. Total immunoglobulin M (IgM), IgG and IgA were detectable in the sputum of subjects. Notably, in patients with mild to moderate COPD, current smoking status was associated with decreased IgM and IgG. Next, using a comprehensive autoantigen array, we measured matched sputum and serum autoantibodies in 224 individuals. Serum autoantibodies were more abundant than sputum autoantibodies and correlated strongly between two independent COPD cohorts. Overall, the autoantibody profile of a patient with COPD was the same as a control subject. A proportion of autoantibody specificities were differentially expressed in patients with COPD with anti-tissue autoantibodies weakly associated with measures of emphysema. Taken together, these data suggested chronic cigarette smoke exposure was associated with limited differential expression of autoantibodies, but these changes were not a reliable method to identify COPD status. In our third study, we assessed the impact of cigarette smoke exposure on the composition and function of pulmonary macrophage subpopulations. Macrophages perform a central role in respiratory host defence and are implicated in the pathobiology of several respiratory diseases. Using a mouse model of cigarette smoke exposure, we reported cigarette smoke-induced expansion of CD11b+ macrophage subpopulations including monocyte-derived alveolar macrophages and interstitial macrophages. The altered pulmonary macrophage composition following cigarette smoke exposure contributed to attenuated fibrogenesis in a model of bleomycin-induced lung injury. This study offered insight to pulmonary macrophage composition and function following cigarette smoke exposure. This thesis summarises the original contributions and work completed during the course of this Ph.D., aimed at understanding the impact of cigarette smoke exposure on immune components central to respiratory disease. In conclusion, these findings shed light on the presence of (auto)antibodies in patients with COPD and the composition of macrophage subpopulations following cigarette smoke exposure.
CIGARETTE SMOKE IMPACT ON RESPIRATORY DISEASE IMMUNOPATHOLOGY
Overall, the work presented in this thesis explored the impact of cigarette smoke on the immunopathogenesis of respiratory disease. This thesis highlighted the determinantal impact of cigarette smoke on (auto)antibody levels and pulmonary macrophage composition. Work completed by Steven P Cass 2016-2021.
Keywords: Cigarette smoke; Respiratory disease; COPD; Autoantibodies; Macrophage; Immunology; Immune system; Tissue remodelling